Девять жизней Греты: [повести] / Анна Данилова - Данилова Анна Васильевна (Grime & Private, 2010)
Экземпляры: ф.4 (20161122) / Инвентарный номер: 2757 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 18 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44